Mimetic Approach In The Poem "To You My Lover" The Work Of Heri Isnaini - Dedi Soepandi (International Journal of Multilingual Education and Applied Linguistics, 2024)
Poetry is a literary work that is imaginative, which analogizes meaning with other expressions so that the meaning contained in poetry is hidden behind aesthetic and fictional words that not everyone understands the direction and purpose of the poetry conveyed. Poetry is not easy for readers to understand at a glance because the language is broad and the meaning is difficult to interpret, therefore a reader must have knowledge in studying poetry literary works in order to understand the meaning conveyed by the poetry. The poem "To You My Lover" by Heri Isnaini is formed from a unique and simple language structure but has a broad meaning and makes readers interested in his work. The romantic and beautiful language is an attraction and makes this poetry by Heri Insaini research material. The aim of this research is to analyze the meaning in the poem entitled "To you" by Heri Isnaini and convey the detailed content of the poem so that readers can understand the meaning conveyed through this research. This research is also useful for readers to further develop literary works in the form of poetry. The method used in this research uses a descriptive method which examines the content of the meaning of the poem "To You My Lover". Apart from that, the poetry in this research was dissected using a mimetic approach. Mimetics is an approach in literary criticism regarding imitation or fiction of real life.